2002
DOI: 10.1038/sj.bjc.6600487
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of stomach cancer death in relation to green tea consumption in Japan

Abstract: To evaluate whether green tea consumption provides protection against stomach cancer death, relative risks were calculated using Cox proportional hazards regression analysis in the Japan Collaborative Study for Evaluation of Cancer Risk, sponsored by the Ministry of Health and Welfare (JACC Study). The study was based on 30 370 men and 42 481 women aged 40 -79. After adjustment for age, smoking status, history of peptic ulcer, family history of stomach cancer along with certain dietary items, the risks associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 15 publications
0
54
0
Order By: Relevance
“…In contrast to laboratory studies and most casecontrol studies, however, all but one recent cohort study have shown no protective effect of green tea for gastric cancer [62][63][64][65]. In a population-based prospective study conducted in Miyagi Prefecture in northern Japan, the RRs associated with drinking one or two, three or four, and fi ve or more cups of green tea per day, as compared with less than one cup per day, were 1.3 (95% CI = 0.8-1.9), 1.2 (95% CI = 0.8-1.8), and 1.5 (95% CI = 1.0-2.1), respectively, in men (for trend, P = 0.03), and 0.8 (95% CI = 0.5-1.5), 0.7 (95% CI = 0.4-1.3), and 0.8 (95% CI = 0.5-1.3), respectively, in women (for trend, P = 0.46) [62].…”
Section: Green Teamentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to laboratory studies and most casecontrol studies, however, all but one recent cohort study have shown no protective effect of green tea for gastric cancer [62][63][64][65]. In a population-based prospective study conducted in Miyagi Prefecture in northern Japan, the RRs associated with drinking one or two, three or four, and fi ve or more cups of green tea per day, as compared with less than one cup per day, were 1.3 (95% CI = 0.8-1.9), 1.2 (95% CI = 0.8-1.8), and 1.5 (95% CI = 1.0-2.1), respectively, in men (for trend, P = 0.03), and 0.8 (95% CI = 0.5-1.5), 0.7 (95% CI = 0.4-1.3), and 0.8 (95% CI = 0.5-1.3), respectively, in women (for trend, P = 0.46) [62].…”
Section: Green Teamentioning
confidence: 99%
“…In a population-based prospective study conducted in Miyagi Prefecture in northern Japan, the RRs associated with drinking one or two, three or four, and fi ve or more cups of green tea per day, as compared with less than one cup per day, were 1.3 (95% CI = 0.8-1.9), 1.2 (95% CI = 0.8-1.8), and 1.5 (95% CI = 1.0-2.1), respectively, in men (for trend, P = 0.03), and 0.8 (95% CI = 0.5-1.5), 0.7 (95% CI = 0.4-1.3), and 0.8 (95% CI = 0.5-1.3), respectively, in women (for trend, P = 0.46) [62]. In a nationwide multicenter prospective study, no inverse association was found between green tea consumption and gastric cancer death, with the risks associated with drinking 1 or 2, 3 or 4, 5-9, and ≥ 10 cups of green tea per day, relative to those of drinking less than 1 cup per day, of 1.6 (95% CI = 0.9-2.9), 1.1 (95% CI = 0.6-1.9), 1.0 (95% CI = 0.5-2.0), and 1.0 (95% CI = 0.5-2.0), respectively, in men (for trend, P = 0.669), and 1.1 (95% CI = 0.5-2.5), 1.0 (95% CI = 0.5-2.5), 0.8 (95% CI = 0.4-1.6), and 0.8 (95% CI = 0.3-2.1), respectively, in women (for trend, P = 0.448) [63]. Furthermore, green tea consumption was virtually unrelated to the incidence of any cancer, including gastric cancer, in a follow-up study of atomic bomb survivors in Hiroshima and Nagasaki [64].…”
Section: Green Teamentioning
confidence: 99%
“…Details of the study design were reported previously (Ohno and Tamakoshi, 2001;Hoshiyama et al, 2002). Briefly, the cohort included 110 792 men and women (46 465 and 64 327, respectively), 40 -79 years old at recruitment, enrolled in 1988 -1990.…”
Section: Jacc Studymentioning
confidence: 99%
“…The relative risk (RR) and its 95% confidence interval (CI) were calculated based on the regression coefficient and its standard error (Cox, 1972), for an indicator term corresponding to the level of an independent variable. For multivariate analysis, several factors were listed as potential confounders according to epidemiological studies (Boeing, 1991;Hoshiyama and Sasaba, 1992;World Cancer Research Fund, 1997;Hoshiyama et al, 2002;Yatsuya et al, 2002). Trends of association were assessed by the regression model assigning scores (0 -4) to the levels of the independent variables.…”
Section: Data Processingmentioning
confidence: 99%